Inhibition of ANXA1 Ameliorates Myocardial Ischemia/Reperfusion Injury by Targeting RAS/Raf/MAPK Axis-Mediated Ferroptosis - Yin Guo MD; Tian-xiao Lou BD; Yang Liu BD; Xin-yu Li MD; Xiao-yu Liu BD; Yi Huang MD (Journal of Cardiovascular Pharmacology and Therapeutics)
Objective: Annexin-A1 (ANXA1) participates in regulating ferroptosis. Ferroptosis is involved in myocardial ischemia-reperfusion injury (MIRI). However, effect and mechanism of ANXA1 in ferroptosis after MIRI remain unclear. Materials and Methods: Gene expression omnibus database was used to screen differentially expressed genes (DEGs), and R package was used to visualize the volcano map and heat map of DEGs in MIRI. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes analyses were used to analyze the related signaling pathways and functions of DEGs. FerrDb database was used to find genes related to ferroptosis. H9c2 cells were cultured under hypoxia/reoxygenation (H/R). Quantitative real-time polymerase chain reaction and western blot detected mRNA and protein expression of relevant genes. Mitochondrial membrane potential was determined by JC-1. Cell viability was assessed using CCK-8. Levels of Fe 2+ , glutathione, malondialdehyde, and reactive oxygen species (ROS) were detected by kits. Results: Genes such as ANXA1 were highly expressed in MIRI compared to normal tissues. Hypoxic cardiomyocytes had enhanced viability after knocking down ANXA1. ANXA1 depletion improved ferroptosis and altered mitochondrial functioning in cardiomyocytes under H/R condition. Ferroptosis inducer Erastin reversed this phenomenon. Phosphorylation levels of c-Jun N-terminal kinase, P38, and Raf in H9c2 cells after ANXA1 silencing were increased. With treatment of RAF inhibitor Sorafenib, above results were reversed. ANXA1 depletion alleviated ferroptosis and mitochondrial damage by activating RAS/Raf/mitogen-activated protein kinase (MAPK) pathway in H/R-induced cardiomyocytes. Conclusions: ANXA1 knockdown reduces cardiomyocyte ferroptosis after MIRI by regulating RAS/Raf/MAPK signaling pathway, which provides new therapeutic targets for MIRI treatment.